The Effect of Working Hours and Incentives on the Quality of Work of PT MNY Employees - Pramudita Ananta Prabowo; Erik Bisri Alamsyah; Eny Rochmatulaili (Universitas Pelita Harapan, 2025)
This study examines the impact of working hours and incentives on employee work quality at PT MNY. A quantitative approach was employed, with a survey method used to collect data from 200 respondents selected through purposive sampling. Structural Equation Modeling (SEM) was utilized to analyze the data. The findings indicate that working hours significantly and positively affect employee work quality (p = 0.035). Effective management of working hours is crucial for enhancing employee performance and productivity. Additionally, incentives were found to have a significant positive effect on work quality (p = 0.034), underscoring the importance of financial and non-financial rewards in motivating employees. The simultaneous analysis revealed that working hours and incentives jointly influence employee quality, with a path coefficient of 0.423 and a significant value of p = 0.005. Balanced work schedules and fair incentive systems are critical in maintaining employee motivation and productivity. The study recommends that PT MNY's management implement balanced work schedules and design a more equitable reward system to optimize employee performance. Future research should consider additional factors, such as leadership style and organizational culture, to gain a more comprehensive understanding of the determinants of employee work quality. By implementing these recommendations, PT MNY can enhance employee motivation, productivity, and overall work quality, contributing to the organization's success. This study provides valuable insights for organizations seeking to improve employee performance and work quality through effective management of working hours and incentives.